Profil Pemahaman Representasi Mikroskopik Mahasiswa IPA pada Materi Larutan Elektrolit dan Non-elektrolit - Candra Kusumaningrum, Aldila (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
Chemistry as one of the natural sciences has the characteristic of abstract concepts where the concepts in chemistry cannot be perceived by the senses so that special visualization is needed. Therefore, to understanding the abstract concept in chemistry, multiple representations are known, namely macroscopic, microscopic, and symbolic representations. This microscopic representation is used to visualize abstract concepts at the molecular level. However, in chemistry learning, especially at the high school level, it is still very rare to find chemistry learning that involves understanding chemical concepts at the microscopic level. So the aim of this study is to determine the profile of microscopic representation understanding of IPA college students as prospective teachers on the material of electrolyte and non-electrolyte solutions. The descriptive quantitative method with a test approach was used as a method in this study and the sample is 72 Tadris IPA college students of IAIN Ponorogo in the 2023/2024 academic year. The results of the study show that in the category of analysis of differences between strong electrolyte and weak electrolyte solutions, students' understanding of microscopic representation is low, while in the category of analysis the solubility of a substance in water, students' understanding of microscopic representation was classified as moderate.